Biological responses in rats exposed to mainstream smoke from a heated cigarette compared to a conventional reference cigarette. (March 2015) - Fujimoto, Hitoshi; Tsuji, Hiroyuki; Okubo, Chigusa; Fukuda, Ichiro; Nishino, Tomoki; Lee, K. Monica; Renne, Roger; Yoshimura, Hiroyuki
Abstract The heated cigarette (HC) generates mainstream smoke by vaporizing the components of the tobacco rod using a carbon heat source at the cigarette tip. Mainstream smoke of HC contains markedly less chemical constituents compared to combusted cigarettes. Mainstream smoke from HC was generated under Health Canada Intense regimen and its biological effects were compared to those of Reference (3R4F) cigarettes, using nose-only 5-week and 13-week inhalation studies. In the 13-week study, SD rats were necropsied following exposure to mainstream smoke from each cigarette at 200, 600 or 1000 µg wet total particulate matter/L for 1 h/day, 7 days/week or following a 13-week recovery period. Histopathological changes in the respiratory tract were significantly lesser in HC groups; e.g. respiratory epithelial hyperplasia in the nasal cavity and accumulation of pigmented macrophages in alveoli. After a 13-week recovery, the lesions were completely or partially regressed, except for accumulation of pigmented macrophages in alveoli, in both HC and 3R4F groups. In the 5-week study, SD rats were necropsied following exposure to mainstream smoke of either cigarette at 600 or 1000 µg/L for 1 h, two times/day (with 30 min interval), 7 days/week or following a 4-week recovery period. Bronchoalveolar lavage fluid (BALF) analysis of neutrophil percentages and enzyme levels like γ-GT, ALP and LDH indicated that pulmonary inflammation was significantly less in HC groups compared to 3R4F groups. In conclusion, HC demonstrated significantly lower biological effects compared to 3R4F, based on the BALF parameters and histopathology.